Prevalence of hypocalcemia in term newborns requiring phototherapy - Pereira, Rochelle A.; Avasthi, Bhupendra; Saste, Sonal; Bavdekar, Sandeep B. (International Journal of Contemporary Pediatrics, 2023)
Background: Neonatal hyperbilirubinemia in the first week of life is one of the most prevalent clinical entity observed, affecting 60% of term-babies and 80% of preterm newborn babies, many requiring intervention in the form of phototherapy. The effect of phototherapy on serum calcium levels has not been studied much in Indian literature. The objectives of this study was to evaluate the prevalence of hypocalcemia in healthy, term newborn babies receiving phototherapy for unconjugated hyperbilirubinemia and to determine the association, if any between serum calcium and birth weight, postnatal age at start of phototherapy, weight at enrolment, gestational age at birth, maternal age and duration of phototherapy. Methods: This was a prospective observational study conducted over a period of 10 months among 80 term neonates admitted to the inpatient department at a tertiary care centre in Mumbai. Total serum calcium and ionised calcium levels were measured at the start of phototherapy and on stopping phototherapy/discharge. Data were analysed using statistical package for social sciences (SPSS) version 21 software. Results: Two (2.5%) out of the 80 neonates were found to have hypocalcemia after phototherapy with serum ionic calcium levels less than 1 mmol/l. Even though a larger proportion of neonates showed a decrease in the serum total calcium (56.25%) and serum ionic calcium (58.75%) levels after phototherapy, none of the neonates developed symptomatic hypocalcemia at those levels. A statistically significant association was found between maternal age in years with the serum total calcium levels after phototherapy and age at starting phototherapy (in hours) with the serum ionic calcium levels after phototherapy. Conclusions: The present study concludes that there is significant decrease in the levels of ionised calcium after phototherapy, however there was no significant decrease in the total serum calcium levels and none of the neonates were symptomatic. Hence, we do not recommend regular serum calcium monitoring in healthy term neonates receiving phototherapy and find no indication for the prophylactic use of calcium supplementation in these neonates.